Risk Factors Associated with Increased Morbidity in Living Liver Donation - Helry L. Candido; Eduardo A. da Fonseca; Flávia H. Feier; Renata Pugliese; Marcel A. Benavides; Enis D. Silva; Karina Gordon; Marcelo Gama de Abreu; Jaume Canet; Paulo Chapchap; Joao Seda Neto (Journal of Transplantation)
Living donor liver donation (LDLD) is an alternative to cadaveric liver donation. We aimed at identifying risk factors and developing a score for prediction of postoperative complications (POCs) after LDLD in donors. This is a retrospective cohort study in 688 donors between June 1995 and February 2014 at Hospital Sírio-Libanês and A.C. Camargo Cancer Center, in São Paulo, Brazil. Primary outcome was POC graded ≥III according to the Clavien-Dindo classification. Left lateral segment (LLS), left lobe (LL), and right lobe resections (RL) were conducted in 492 (71.4%), 109 (15.8%), and 87 (12.6%) donors, respectively. In total, 43 (6.2%) developed POCs, which were more common after RL than LLS and LL (14/87 (16.1%) versus 23/492 (4.5%) and 6/109 (5.5%), resp., p<0.001). Multivariate analysis showed that RL resection (OR: 2.81, 95% CI: 1.32 to 3.01; p=0.008), smoking status (OR: 3.2, 95% CI: 1.35 to 7.56; p=0.012), and blood transfusion (OR: 3.15, 95% CI: 1.45 to 6.84; p=0.004) were independently associated with POCs. RL resection, intraoperative blood transfusion, and smoking were associated with increased risk for POCs in donors.